Protective effects of BAIBA and thymoquinone in type 1 diabetic nephropathy: modulation of Irisin, NF-?B, and Caspase-3 expression - Pekince Ozoner, Merve; Gur, Fatih Mehmet; Aktas, Ibrahim; Ozoner, Ozgur; Timurkaan, Sema (Springer, 2026)
Diabetes is closely related to increased production of reactive oxygen species, which leads to oxidative stress, chronic inflammation, and increased apoptosis, especially in kidney tissues. Irisin is a recently discovered myokine with the potential to offer hope for the treatment of many metabolic diseases, while BAIBA is also a newly identified endogenous protective myokine. In this study, the effects of thymoquinone (TIM), known for its antioxidant activity, as well as the possible agonistic interaction between irisin and BAIBA on cellular stress and apoptosis occurring in diabetic kidneys were investigated using immunohistochemical methods. In this study, 35 Sprague Dawley rats were equally separated into five groups: Control, STZ, TIM, BAIBA and STZ + TIM + BAIBA. Type 1 diabetes was induced by a single intraperitoneal injection of streptozotocin (STZ, 50 mg/kg). The same protocol was applied to induce diabetes in the TIM and BAIBA groups. Following induction, TIM (20 mg/kg) and BAIBA (100 mg/kg) were administered daily via gavage for five weeks. In the STZ + TIM + BAIBA group, diabetes was induced similarly, followed by daily oral administration of a combination of TIM and BAIBA at the same doses for five weeks. At the conclusion of the study, kidney samples were obtained and analysed using both histochemical and immunohistochemical methods. Results demonstrated that TIM significantly reduced intersitial fibrosis by 55% in the kidneys. It is revealed that both TIM and BAIBA reduced NF-kappa B immunointensity by 63% and when used simultaneously by %48. Caspase3 immunointensity was reduced by 38%, 46% and 26% following TIM, BAIBA and TIM + BAIBA administration respectively. Also both TIM and BAIBA was observed to cause positive up-regulation on irisin expression. The findings of this study demonstrated that TIM and BAIBA effectively prevented renal fibrosis and apoptosis in STZ-induced diabetic rats, particularly through the downregulation of NF-kappa B.
Keywords: BAIBA; Thymoquinone; Irisin; NF-kappa B; Apoptosis